2005
DOI: 10.1007/s00415-005-0943-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of quetiapine in psychotic Parkinsonian patients with and without dementia

Abstract: In this open trial, quetiapine was not beneficial in the ITT group using the BPRS, although families reported improvement in about 30% of patients (CGIS). Among patients who completed the study, quetiapine was more effective in the PDNODEM group. A double blind study with quetiapine is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…In a sample in which three participants with PDD were treated with olanzapine (44) Quetiapine. The highest level of evidence for quetiapine was from a case series in DLB, a retrospective chart review in PDD, and a randomized controlled trial in Lewy body dementia (47)(48)(49). Reductions in psychiatric symptoms were reported for six of nine individuals with DLB following treatment with quetiapine (change in sum of NPI scores on the delusions, hallucinations, and agitation/aggression subscales, 7.7 points) (47).…”
Section: Antipsychoticsmentioning
confidence: 97%
See 1 more Smart Citation
“…In a sample in which three participants with PDD were treated with olanzapine (44) Quetiapine. The highest level of evidence for quetiapine was from a case series in DLB, a retrospective chart review in PDD, and a randomized controlled trial in Lewy body dementia (47)(48)(49). Reductions in psychiatric symptoms were reported for six of nine individuals with DLB following treatment with quetiapine (change in sum of NPI scores on the delusions, hallucinations, and agitation/aggression subscales, 7.7 points) (47).…”
Section: Antipsychoticsmentioning
confidence: 97%
“…However, 33% of participants withdrew because of adverse events. For individuals with PDD and drug-induced psychosis, quetiapine was associated with worsening cognition and motor function without improvements to psychiatric status (48). A randomized placebocontrolled trial of quetiapine in Lewy body dementia (DLB, N523; PDD, N59; Alzheimer's disease with parkinsonian features, N58) revealed no between-group differences on measures of psychiatric symptoms, cognition, activities of daily living, motor function, or clinician's impression of change (49).…”
Section: Antipsychoticsmentioning
confidence: 97%
“…In addition, risperidone, olanzapine, ziprasidone and aripiprazole have frequently been associated with dose-dependent neuroleptic induced parkinsonism in otherwise normal psychotic patients (personal observation). Open label studies showed quetiapine to be well tolerated and an effective antipsychotic for PDP [96][97][98] and in comparison trial [95] to be non-inferior to clozapine. Unfortunately, three double blind controlled trials did not find efficacy [99][100][101], although all confirmed that the drug was free of motor worsening.…”
Section: Managementmentioning
confidence: 99%
“…Rivastigmine would be selected first by most clinicians [1], using the once a day transdermal patch if available rather than the oral twice a day tablet, with donepezil and galantamine as alternative. A low dose of an atypical antipsychotic may be required at any point if the neuropsychiatric symptoms (particularly delusions and agitation/agressivity) require immediate treatment: the best evidence is for clozapine [2] but clinically most clinicians will use quetiapine despite the lack of evidence from randomized clinical trials, principally because the doses can be increased progressively from 12.5 mg upwards without the need for hematologic monitoring [3,4]. Although risperidone and olanzapine are atypical neuroleptics, they should not be used as they have been associated with clinically significant deterioration of the motor signs of parkinsonism in patients with PDD.…”
Section: Pharmacotherapy Of Parkinson Disease Dementiamentioning
confidence: 99%